2009
DOI: 10.1111/j.1749-6632.2009.03956.x
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin Family Peptides and Receptors in Mammalian Brain

Abstract: As a foundation for regulatory and functional studies of central relaxin family peptide receptor systems, we are mapping the distribution of the different receptors in the brain of rat, mouse, and nonhuman primates, attempting to identify the nature of the receptor-positive neurons in key circuits and establish the complementary distribution of the respective ligands in these species. Here we review progress in mapping RXFP1, RXFP2, and RXFP3 (mRNAs and proteins) and their respective ligands and discuss some o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 38 publications
(87 reference statements)
2
45
0
Order By: Relevance
“…Thus both anatomical and physiological evidence supports a pathway, whereby circulating RLX results in activation of neurons in the SFO with subsequent neuroendocrine and autonomic effects mediated by projections to structures within the blood-brain barrier, such as the PVN and SON (4). Relatively little is known about the function of CNS RXFP1 receptors inside the blood-brain barrier, although it has been suggested that RLX peptide systems within the brain may subserve a local neuromodulatory function (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus both anatomical and physiological evidence supports a pathway, whereby circulating RLX results in activation of neurons in the SFO with subsequent neuroendocrine and autonomic effects mediated by projections to structures within the blood-brain barrier, such as the PVN and SON (4). Relatively little is known about the function of CNS RXFP1 receptors inside the blood-brain barrier, although it has been suggested that RLX peptide systems within the brain may subserve a local neuromodulatory function (21).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in plasma osmolality and osmotic threshold for AVP secretion normally seen in the first half of pregnancy occurs simultaneous to increased plasma RLX (52), and a decrease in osmolality does not occur in ovariectomized or RLX-immunoneutralized P rats (38). Immunoneutralization of RLX (icv) in the second half of rat pregnancy (days [12][13][14][15][16][17][18][19][20][21][22] blocks the increase in water consumption that is normally mediated by an effect of RLX in the forebrain at this time (58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in situ hybridization (Piccenna et al, 2005) and radioligand binding studies (Ma et al, 2006) have revealed that RXFP1 mRNA/binding sites are broadly distributed within the rodent brain including high densities in the olfactory bulb, cortex, hippocampus and subiculum, amygdala, circumventricular organs, thalamus, hypothalamus, and brainstem (Ma and Gundlach, 2007; Gundlach et al, 2009). This broad distribution suggests that relaxin/RXFP1 signaling modulates a diverse range of neural circuits, although the nature of this modulation and the relative role of endogenously/locally produced relaxin vs. any effects of circulating relaxin are not known.…”
Section: Resultsmentioning
confidence: 99%
“…Potential roles in appetite regulation, stress response, as well as memory and learning have been described (Tanaka et al, 2005;Nunez et al, 2006;Gundlach et al, 2009). The expression of relaxin-3 is restricted to the central nervous system, while the receptor RXFP3 besides brain is also expressed at low levels in most peripheral organs analysed, but the function of the receptor in peripheral organs is not known.…”
Section: Discussionmentioning
confidence: 97%